KLRC3, a Natural Killer receptor gene, is a key factor involved in glioblastoma tumourigenesis and aggressiveness. Issue 2 (19th September 2016) - Cheray, Mathilde; Bessette, Barbara; Lacroix, Aurélie; Mélin, Carole; Jawhari, Soha; Pinet, Sandra; Deluche, Elise; Clavère, Pierre; Durand, Karine; Sanchez‐Prieto, Ricardo; Jauberteau, Marie‐Odile; Battu, Serge; et al.
Abstract: Glioblastoma is the most lethal brain tumour with a poor prognosis. Cancer stem cells (CSC) were proposed to be the most aggressive cells allowing brain tumour recurrence and aggressiveness. Current challenge is to determine CSC signature to characterize these cells and to develop new therapeutics. In a previous work, we achieved a screening of glycosylation‐related genes to characterize specific genes involved in CSC maintenance. Three genes named CHI3L1, KLRC3 and PRUNE2 were found overexpressed in glioblastoma undifferentiated cells (related to CSC) compared to the differentiated ones. The comparison of their roles suggest that KLRC3 gene coding for NKG2E, a protein initially identified in NK cells, is more important than both two other genes in glioblastomas aggressiveness. Indeed, KLRC3 silencing decreased self‐renewal capacity, invasion, proliferation, radioresistance and tumourigenicity of U87‐MG glioblastoma cell line. For the first time we report that KLRC3 gene expression is linked to glioblastoma aggressiveness and could be a new potential therapeutic target to attenuate glioblastoma.